2011
DOI: 10.2478/v10045-011-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Molecular Variability in Rhizoctonia Bataticola, the Incitant of Root Rot Disease of Pulse Crops

Abstract: Abatract:The present study explored pathogenic and genetic variability among the eleven isolates of Rhizoctonia bataticola (Taub.) Butler from different pulse crops. Based on morphological characters, 11 isolates were categorized into three groups viz., linear, fluffy, and linear at the end with fluffy growth at the center. Isolates also showed variability in sclerotial characters (intensity and shape) and intensity of pigment synthesis. All isolates were more aggressive on the original host from which it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…RAPD-PCR has been successfully used for studying inter and intra-specific variability among populations from different as well as the same geographical regions (Sundravadana et al, 2011). The results of our present study indicate significant level of variation among the 22 isolates of R. solani.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…RAPD-PCR has been successfully used for studying inter and intra-specific variability among populations from different as well as the same geographical regions (Sundravadana et al, 2011). The results of our present study indicate significant level of variation among the 22 isolates of R. solani.…”
Section: Discussionsupporting
confidence: 55%
“…Perhaps, evaluation of the genetic diversity in pathogen isolates has been an initial step towards understanding the population structure. Molecular techniques have become reliable and are highly suitable tools for identifying pathogen species and for assessing genetic variation within collections and populations (Sundravadana et al, 2011). With the advent of various molecular marker technologies, the studies of genetic diversity in plant pathogens have become feasible.…”
Section: Agroecological Zone Isolatementioning
confidence: 99%
“…The use of molecular marker to study the genetic diversity relationships among populations from different as well as the same geographical regions (Sundravadana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse Rice sheath blight isolates has been studied by morphological characterization and pathogenicity testing and also by various molecular techniques reliable and are highly suitable tools for identifying pathogen species and analyzing the genetic variations of microorganisms (Sundravadana et al, 2011). RAPD (Random Amplified Polymorphic DNA) markers have been successfully used to determine the numerous filamentous fungi species collected from different fields of experimental mycology (Pollastro et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques have become reliable and are highly suitable tools for identifying pathogen species and for assessing genetic variation within collections and populations (Sundravadana et al, 2011). Recently, Banerjee et al (2012) reported that the RAPD can still be considered as a reliable, efficient and effective marker technology for determining genetic relationships in Rhizoctonia spp.…”
mentioning
confidence: 99%